CRUSTAL STRUCTURE, FLEXURE, AND SUBSIDENCE HISTORY OF THE HAWAIIAN-ISLANDS - Watts, A; Tenbrink, U (1989)
Seismic reflection profile data have been used to estimate the long-term (>106yr) mechanical properties of the oceanic lithosphere underlying the Hawaiian Islands. The data show prominent reflectors associated with the top of the oceanic crust (reflectors 2), the M discontinuity, and the base of the crust (reflector 3). The two-way travel time to the reflectors has been depth converted using velocity depth functions derived from seismic refraction expanding spread profile data and compared to calculated depths based on simple three-dimensional elastic plate models. A good fit to the reflector depths was obtained for a model with an effective elastic thickness of the lithosphere Te of 40km. The main discrepancies with the refraction data occur beneath Oahu and Molokai where the predicted depth of the base of the flexed crust is too shallow and beneath the southeast flank of Hawaii where it is too deep. We attribute the thickened crust beneath Oahu to ponding of magma at the base of the crust following the last phases of tholeiitic shield building and the thinned crust beneath the flanks of Hawaii to crustal melting beneath the youngest part of the chain. -from Authors